Anti-obesity medication (naltrexone/bupropion) in obesity management: single-centre early experience - Tan, Siow Foon; Mukhtar, Firdaus; Ng, Ooi Chuan; Mohd Yusof, Barakatun Nisak; Muhammadun Basar, Nur Adilah; Changrabose, Thanalactchumy; Cheng, Xiang Jun; Nor Hanipah, Zubaidah (Penerbit Universiti Sains Malaysia, 2025)
Background: Naltrexone/bupropion is a recently approved antiobesity medication in Malaysia. We aimed to determine the 12-week outcomes of naltrexone/bupropion as an antiobesity medication at our centre. Methods: This was a single-centre, prospective, pilot, observational study. All patients prescribed naltrexone/bupropion at Metabolic and Obesity Clinic, Hospital Sultan Abdul Aziz Shah, Universiti Putra Malaysia, between July 2023 and January 2024 were identified. The collected data included demographics, comorbidities, baseline weight, and body mass index. At the 12-week follow-up, data on weight, body mass index, side effects, and anti-craving effects were documented. Data are presented as mean ± standard deviation (SD) for continuous variables and as count and frequency for categorical variables. Results: Eighteen patients were treated with naltrexone/bupropion during the study. The majority were female (n = 13, 72%) and Malay (n = 13, 72%), with a mean age of 45 years (SD = 10). The mean body mass index was 38 kg/m2 (SD = 8). Comorbidities included diabetes (n = 9, 50%), hypertension (n = 7, 39%), and dyslipidaemia (n = 11, 61%). Of the 14 patients (78%) who completed 12 weeks of follow-up, the mean weight loss was 2.11 kg (SD = 2.61, P = 0.01), and the percentage of total body weight loss was 2%. The main side effects were giddiness (50%), nausea (44%), and headaches (38%). Naltrexone/bupropion was effective in reducing cravings in 75% of the patients. 63% of patients experienced side effects, which slowed escalation. Conclusion: Our early experience with naltrexone/bupropion as an antiobesity medication suggests that it is effective in managing obesity with craving symptoms. A longer follow-up with a larger group of patients is necessary before a definitive conclusion can be made.